2000
DOI: 10.1177/0003489400109s1242
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fast Forword™ to Enhance Language Development in Children with Cochlear Implants

Abstract: 10-■-Receptive-O-Expressive Pre 6 mo Evaluation Interval 12 mo Mean age equivalent language scores on Reynell Developmental Language Scales-Revised for 18 prelingually deafened children at preoperative interval with hearing aids (Pre) and 6 and 12 months after implantation with Clarion cochlear implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Thus, only 7, 7 and 3 articles were selected from the databases, respectively, LILACS, SciELO and IBECS. During this phase, 12 studies found in more than one database Regarding the publication year, the studies began to appear in the year 2000 with three publications [12][13][14] . Between 2002 and 2005 no publication of this kind was found.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, only 7, 7 and 3 articles were selected from the databases, respectively, LILACS, SciELO and IBECS. During this phase, 12 studies found in more than one database Regarding the publication year, the studies began to appear in the year 2000 with three publications [12][13][14] . Between 2002 and 2005 no publication of this kind was found.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the participants of these studies (Table 1), between 2 and 10 individuals participated in eight studies [16][17][18][19][20][21][22][23] ; 11 to 20 individuals participated in seven studies 12,14,[24][25][26][27][28] . Seven studies had more than 21 participants 13,[29][30][31][32][33][34] , in which three publications 29,31,33 had hearing participants as direct target of the interventions (e.g., parents, teachers and CI users caretakers) aiming to evaluate its indirect effects on deaf children and CI users' rehabilitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the vowel accuracy model was best used as a supplementary tool rather than as a primary means of improving speech production. Schopmeyer et al (2000) provide the strongest evidence to date in support of the use of computer technology in the habilitation of students with cochlear implants. The authors investigated the efficacy of using the Fast ForWord software program to enhance the language development of 11 children with cochlear implants.…”
Section: Introductionmentioning
confidence: 98%
“…Earobics, Cognitive Concepts, Evanston, Illinois; Fast ForWord, Scientific Learning Corporation, Berkley, California). The papers by Pratt et al (1993) and Schopmeyer et al (2000) provide some preliminary evidence to support the use of computer software with children with cochlear implants. Pratt et al (1993) investigated the interaction between exposure to the vowel accuracy model of the IBM SpeechViewer software and change in the vowel productions of five young children aged 3 to 5 years who used hearing aids.…”
Section: Introductionmentioning
confidence: 99%